Clinical significance of molecular diagnosis of pilocytic astrocytoma: A Case Report - Ono, Takahiro; Takahashi, Masataka; Hatakeyama, Junya; Oda, Masaya; Sahm, Felix; Nanjo, Hiroshi; Deimling, Andreas von; Shimizu, Hiroaki (NMC Case Report Journal, 2019)
This paper reports on a case of pilocytic astrocytoma (PA), for which a diagnosis by conventional pathological diagnosis was difficult but an accurate diagnosis was possible by a new molecular diagnostic method. A 13-year-old girl whose tumor developed by a headache that gradually worsened, and a well-demarcated T2-hyperintense lesion was found in the left cerebellum by a magnetic resonance imaging while the apparent diffusion coefficient value was also high. While the finding was a typical PA, histological features of PA were not found in the surgical specimen. An initial diagnosis was anaplastic astrocytoma (AA), and the final diagnosis through a central review was diffuse astrocytoma (DA). On the other hand, using MethylationEPIC (850 K) array, an analysis by a DNA methylation-based tumor classifier tool as reported by Capper et al. showed that this case belonged to a methylation class of PA. The copy number profile calculated from the methylation array data showed hints of BRAF/KIAA1549 fusion and no other chromosomal alterations, which also supported the molecular diagnosis. The patient was treated with local radiotherapy concomitant with temozolomide based on the initial pathological diagnosis during the consultation, but maintenance temozolomide therapy was not done according to the final molecular diagnosis. The tumor showed no recurrence for 20 months. In this case, the integrated diagnostic approach based on histological and molecular findings was clinically significant to select proper adjuvant treatment. It is crucial that the usefulness and robustness of this new molecular diagnostic method be validated further.
Gesehen am 04.12.2020